Reader’s Acceptance on The Online News of The Rain Handler at The Mandalika MotoGP Circuit - Putri Balqis; Filosa Gita Sukmono (Jogjakarta Communication Conference (JCC), 2023)
This research was conducted with the aim of knowing reader acceptance of online news on the DetikNews page regarding the Rain Handler's actions at the Mandalika MotoGP Circuit. This type of descriptive qualitative research uses the reception analysis method. The theory used in this study is acceptance theory. Informants in this study are active readers of online news pages. In the study there were four informants. The results of the study concluded that there were three informants in a negotiated position, who understood and accepted the content of the news but had their own opinions. where, there were three informants who stated that they did not fully believe in the actions of rain handlers, but supported the news about rain handlers to the world to introduce Indonesian cultural traditions and local wisdom, while there was one informant who was in the position of opinion, which means that there was one informant who did not fully trust the content of the news about the action of the rain handler and considered the news of the rain handler to close the most important part of the event  MotoGP.